A Study of Epstein-Barr Virus BRLF1 Activity in a Drosophila Model System - Amy Adamson; Dennis LaJeunesse (The Scientific World Journal)
Epstein-Barr virus, a member of the herpesvirus family, infects a large majority of the human population and is associated with several diseases, including cancer. We have created Drosophila model systems to study the interactions between host cellular proteins and the Epstein-Barr virus (EBV) immediate-early genes BRLF1 and BZLF1. BRLF1 and BZLF1 function as transcription factors for viral transcription and are also potent modifiers of host cell activity. Here we have used our model systems to identify host cell genes whose proteins modulate BRLF1 and BZLF1 functions. Via our GMR-R model system, we have found that BRLF1 expression results in overproliferation of fly tissue, unlike BZLF1, and does so through the interaction with known tumor suppressor genes. Through an additional genetic screen, we have identified several Drosophila genes, with human homologs, that may offer further insights into the pathways that BRLF1 interacts with in order to promote EBV replication.